PENGARUH WAKTU PERPINDAHAN PAKAN ALAMI KE PAKAN BUATAN BERENZIM TERHADAP SINTASAN, PERTUMBUHAN PADA PEMELIHARAAN LARVA IKAN BAUNG (Mystus nemurus cv) - Siti Aysah M (Fish Scientiae, 2019)
This study aimed to determine the switching time from natural food to artificial food with the addition of mix enzyme in baung larval rearing. The results showed that the survival rate of baung larvae had the highest score in treatment E (natural feed Artemia salina aged 3 days to 7 days followed by artificial feed in the form of pasta until age 30 days), did not differ with treatment A. Treatment A (Natural Food Artemia salina was given at the age of 3 days to 8 days and then followed by artificial food (shrimp flour +mix enzyme) from the age of 9 days to 15 days artificial feeding was continued until theage of 30 days) showed the highest absolute growth was 0.62 grams and the value of relative growth rate of 14.25 grams did not differ with B, C and E treatments. The highest Individual weight, protein content and mix enzyme activity on all measurement of baung larvae found in treatment A. Water quality of maintenance media of eel was the temperature 27,33oC, pH 7,86, dissolve oxygen 4,76 mg/l and ammonia 0,93 mg/l.